Correlation of cyto-histological findings in a patient with carcinosarcoma - Fava, A (Citotech Online - Case Review, 2023)
The study shows a case of a 74 years-old woman, whose only clinical data was suspicion of carcinosarcoma. An exfoliative cytology and biopsy were performed and sent to laboratory for study. Cytology showed atypical cells with arrangement in “moruloid” groups, cytoplasmic vacuolization and marked nuclear pleomorphism. Similar observations were found with biopsy. Immunohistochemical studies were positive for Cytokeratin 7, PAX 8, Vimentin, CD 10, Desmin and p53. Cytological, histological and immunohistochemical findings were compatible with diagnosis of Carcinosarcoma (Malignant Mixed Müllerian Tumor). This neoplasm is very rare, it usually occurs in postmenopausal women, causing bleeding and abdominal pain, and its treatment is chemotherapy and radical hysterectomy.